Efficient algorithms for multilevel power estimation of VLSI circuits. - Bachmann, W.W (IEEE Transactions on VLSI systems)
This paper presents a methodology for calculating highly accurate mean power estimates for integrated digital CMOS circuits. A complementary calibration scheme for ASIC library cells to extract the power relevant parameters is proposed. The circuit models presented allows the prediction of mean power dissipation of gate-level designs in CMOS technologies with an accuracy that is comparable to a SPICE simulation but up to 10 000 times faster. The outlined approach is capable of handling complex circuits consisting of more than 20 000 cells and thousands of memory elements. Very large sets of input data with several millions of patterns can, thus, be simulated in an efficient way. This allows the prediction of mean power dissipation of VLSI circuits in a realistic functional context which provides new assessment possibilities for digital CMOS low-power design methods. Experimental results for some benchmark circuits are detailed in order to demonstrate the significant improvements in terms of performance, accuracy, and flexibility of this approach compared to state-of-the-art power estimation methods